Single-Sensor Passive Ranging of Underwater Monopoles Using Near-Field/Far-Field Energy Contrasts - MAHMOUD, Saier; SALEH, Louay; CHOUAIB, Ibrahim (Archives of Acoustics, 2025)
While acoustic vector sensors (AVS) are well-established for detection and direction-of-arrival (DOA) estimation using co-located pressure and particle motion (PM) measurements, their potential for passive range estimation remains largely unexplored. This paper introduces a novel single-AVS method for passive range estimation to an acoustic monopole source by exploiting the fundamental near-field dominance of PM energy. We derive the frequency and the distance dependent ratio (ξ) of kinetic to potential acoustic energy density – a key near-field signature inaccessible to conventional hydrophones. By leveraging simultaneous AVS pressure and PM velocity measurements, our method estimates ξ, inverts the monopole near-field model to obtain the Helmholtz number, and directly computes the range. Crucially, we demonstrate that PM sensors offer a potential signal-to-noise ratio (SNR) advantage over pressure sensors within the near-field (>7.8 dB). Validation under simulated noise conditions shows accurate range estimation (RMSE <10 %) for low-frequency sources (<100 Hz) within 8 m–25m ranges at 0 dB SNRs, with performance degrading as frequency increases or SNR decreases. Critically, robustness is confirmed using recorded basin noise profiles, overcoming the isotropic Gaussian noise assumption. This technique extends AVS functionality beyond DOA, enabling single-sensor passive ranging without arrays, environmental priors, or reference signals where conventional methods fail.